Hospitalization cost at childbirth: Health parameters and colonization with antimicrobial resistant bacteria and methicillin susceptible Staphylococcus aureus. (August 2017) - Adler, Alexandra C.; Zamfir, Mihai; Hendrowarsito, Lana; Dammeyer, Antchen; Schomacher, Lasse; Karlin, Barbara; Franitza, Manuela; Nasri, Lilia; Hörmansdorfer, Stefan; Tuschak, Christian; Valenza, Giuseppe; Ewert, Thomas; et al.
Abstract: Objective: Antimicrobial resistant bacteria (AMR) are of public health and economic relevance. However, there is a lack of data regarding AMR colonization in pregnant women and in newborns. Furthermore, there are few studies analyzing hospital's net income (revenues and costs). Study design: The cross-sectional study took place in two Bavarian clinics. Available data regarding women and newborns were collected using a standardized questionnaire, personal IDs and medical records in addition to AMR/MSSA screening. Economic data consisted of estimated hospitalization costs, calculated using a billing system called G-DRG (German-Diagnosis Related Groups) as well as real hospitalization costs (e.g. staff, medical and non-medical infrastructure costs). Results: Data from 635 pregnant women and 566 newborns were included. While AMR colonization has shown no significant association with clinical complications, or net hospital income; primipara status and medical condition during pregnancy did. AMR colonization did not have a significant influence on the health status of pregnant women or of the newborns. Net hospital income for pregnant women was mostly negative in 2014. In 2014 and 2015 the majority of the cases had a net income between ±€ 1000. Newborns with clinical complications differed significantly in Apgar score at 1 min, weight, body length and AMR colonization of the pregnant woman and/or the newborn (p < = 0.05). Conclusion: Results indicate that colonization does not lead to increased costs during hospitalization considering real hospitalization costs as well as G-DRG estimated costs. Both DRG groups had similar MSSA and AMR prevalence and health status. In future studies, a Centralized Cost Accounting as billing method and an improved possibility of AMR coding in G-DRG catalog would be desirable.